The relationship between healthy eating index and Mediterranean diet adherence score with inflammatory indices and disease severity: a case-control study of hospitalized COVID-19 patients - Reihaneh Mousavi; Somayeh Rostami; Saba Shourideh Yazdi; Akram Kooshki; Elaheh Foroumandi (BMC Nutrition)
Abstract Background Recent studies have focused on the connection between nutrition, inflammation, and infectious diseases. This study was conducted to investigate the relationship between the Mediterranean diet adherence score (MDS) and the healthy eating index (HEI) with some clinical findings of patients with COVID-19. Methods This case–control study was conducted in 29 Bahman hospital of Tabriz, Iran, from June to December 2022. Totally, 300 individuals (150 patients with COVID-19 as cases and 150 subjects who had not affected by COVID-19 as controls) was selected using convenience random sampling method to participate in the study. The 138-items food frequency questionnaire-derived dietary data were applied to compute HEI and MDS. Serum levels of BUN, creatinine and inflammatory markers including the Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were measured. Results Both the HEI and MDS of case group was significantly lower than control group (p < 0.001). The MDS was negatively associated with hospitalization duration (R=-0.209, P < 0.001) and serum ESR level (R=-0.420, P < 0.001). A negative relationship was also seen between ESR level and HEI (R=-0.13, P = 0.017). Conclusion It is concluded that higher MDS and HEI contribute to lower inflammatory markers and then diminished risk of covid-19 infection.